Devolution and the Scottish Conservatives : banal activism, electioneering and the politics of irrelevance - Smith, Alexander Thomas T. (Alexander Thomas Telford) (New ethnographies., 2011)
This is a study of devolution and Scottish politics as well as party political activism more generally. It explores how Conservative Party activists who had opposed devolution and the movement for a Scottish Parliament during the 1990s attempted to mobilise politically following their annihiliation at the 1997 General Election.